Penerapan Metode Kooperatif Jigsaw Untuk Meningkatkan Hasil Belajar IPS Siswa Kelas VII SMP Negeri 3 Bontang - Siti Solichah (Jurnal Pendidikan : Riset dan Konseptual, 2020)
ABSTRAK The background of this research is as a solution to the problems experienced by the author when teaching material Human Activities in meeting needs. Students are still having difficulty mastering a lot of material. This paper aims to determine the effectiveness of the application of the jigsaw cooperative method in improving the learning outcomes of students of Class VIIA Begeri 3 Bontang Middle School in social studies subjects. The problems examined are, (1) improvement of student learning outcomes in social studies subject KD Human Activities in meeting the needs (2) the effectiveness of the application of the Jigsaw Cooperative Method to Improve Student Learning Outcomes Class VII A This type of research is classroom action research which consists of two cycles. The subjects of this study were 35 grade VII A students of SMP Negeri 3 Bontang. Researchers obtained data from test and non-test techniques. The test technique in the form of competency tests Human Activity in meeting the needs of non-technical techniques obtained from teacher observation. Data analysis was performed with quantitative and qualitative analysis. The results of this study indicate that the application of the Jigsaw cooperative method in Social Studies learning for Class VII A students changes from cycle I to cycle II. The increase is indicated by an increase in value in each aspect. The average value of the Social Studies KD Student Learning Outcomes test in meeting the needs of the first cycle in the first meeting of the class average of 59.9 and increased at the second meeting to 68 or still in the poor category. The class average in the second cycle of 74.7 in the first meeting was enough to increase to 80.2 (good category) in the second meeting. Based on the results of the study, the researcher recommends that IPS subject teachers apply the jigsaw cooperative method in KD Human Activity learning in meeting needs.